Composite, catalyst ink, and method for producing the composite
A composite of molybdenum disulfide and palladium particles addresses the need for efficient catalyst materials by maintaining a two-dimensional structure and high catalytic activity, achieving enhanced performance in hydrogen generation and water electrolysis.
Patent Information
- Application Number
- JP2024521302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-02
- Filing Date
- 2023-08-02
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-08-02
AI Technical Summary
There is a need for new catalyst materials containing molybdenum disulfide that can effectively utilize its high catalytic activity while maintaining a two-dimensional sheet-type structure and being resource-abundant.
A composite is formed by combining molybdenum disulfide particles with palladium particles, where the average crystallite size of molybdenum disulfide is 150 nm or less, palladium particles are 20 nm or less, and the composite has a specific surface area of 10-200 m^2/g, with palladium content ranging from 0.1% to 20% by mass, and molybdenum disulfide content being predominantly 50-99.9% by mass.
The composite exhibits excellent catalytic performance, particularly in hydrogen generation reactions, with improved catalytic sites and mass transfer, enhancing the efficiency of water electrolysis and catalyst ink applications.
Smart Images

Figure 0007605373000002 
Figure 0007605373000003 
Figure 0007605373000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite, a catalyst ink, and a method for making the composite. This application claims priority based on Japanese Patent Application No. 2022-123199, filed on August 2, 2022, the contents of which are incorporated herein by reference. [Background technology]
[0002] Water electrolysis technology is attracting attention as a technology that can produce hydrogen from water using renewable energy electricity, with the aim of resolving environmental and energy resource issues. Layered transition metal chalcogen compounds, such as molybdenum disulfide (MoS2), are expected to be materials with high catalytic activity while being inexpensive and abundant in resources.
[0003] Patent Document 1 discloses a method for producing molybdenum disulfide doped with metal ions, in which the metal cations of the doped metal are uniformly dispersed between the layers of molybdenum disulfide, and the material retains the two-dimensional sheet structure of molybdenum disulfide in its crystal structure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] China Patent Application Publication No. 106608652 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is still room for improvement in providing new catalytic materials containing molybdenum disulfide. An object of the present invention is to provide a composite, a catalyst ink, and a method for producing the composite, which can be used as a catalyst. [Means for solving the problem]
[0006] The present invention has the following aspects.
[0007] <1> Molybdenum disulfide particles and palladium particles, A composite, wherein the molybdenum disulfide contained in the molybdenum disulfide particles has an average crystallite size of 150 nm or less, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement. <2> The average particle size of the palladium particles is 20 nm or less. <1> The complex according to claim 1, <3> the palladium particles are present on the surface of the molybdenum disulfide particles; <1> or <2> The complex according to claim 1, <4> The palladium particles include an aggregate of palladium atoms having no crystal structure. <1> ~ <3> 2. The complex according to claim 1 , <5> The median diameter D of the complex is determined by dynamic light scattering. 50 is 1000 nm or less. <1> ~ <4> 2. The complex according to claim 1 , <6> The specific surface area of the composite, as measured by the BET method, is 10 m 2 / g or more 200m 2 / g or less. <1> ~ <5> 2. The complex according to claim 1 , <7> The ratio of the palladium content to the total mass of the composite determined by XRF analysis is 0.1 mass% or more. <1> ~ <6> 2. The complex according to claim 1 , <8> The molybdenum disulfide contained in the molybdenum disulfide particles comprises a 3R crystal structure. <1> ~ <7> 2. The complex according to claim 1 , <9> The primary particles of the molybdenum disulfide particles have a shape of a string, ribbon or sheet and an average thickness of 50 nm or less. <1> ~ <8> 2. The complex according to claim 1 , <10> The above <1> ~ <9> 13. A catalyst ink comprising the composite according to any one of claims 1 to 12 and a solvent. <11> The method includes a step of mixing molybdenum disulfide particles and a palladium solution, The molybdenum disulfide particles contain molybdenum disulfide, and the molybdenum disulfide particles have an average crystallite size of 150 nm or less, which is determined from a peak at 2θ=14.4°±0.5° by X-ray diffraction measurement. <1> ~ <9> 13. A method for producing the complex according to any one of the preceding claims. Effect of the Invention
[0008] According to the present invention, it is possible to provide a composite, a catalyst ink, and a method for producing the composite, which can be used as a catalyst. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of an apparatus used for producing molybdenum trioxide particles, which are a raw material for the molybdenum disulfide particles according to an embodiment of the composite. [Diagram 2] FIG. 1 is a diagram showing X-ray diffraction (XRD) profiles of the particles obtained in Synthesis Example 1, Examples 1 to 4, and Comparative Example 1, superimposed on each other. [Diagram 3] 1 shows transmission electron microscope (TEM) images of the particles obtained in Synthesis Example 1, Examples 1 to 4, and Comparative Example 1. [Figure 4] 1 shows a high-resolution transmission electron microscope (HR-TEM) image of the composite particles obtained in Example 2, and an image showing the results of elemental mapping by energy dispersive X-ray spectroscopy (EDS). [Diagram 5] 2 shows an HAADF-STEM image (transmission electron image) and an SEI image (secondary electron image) of the composite particle obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the composite, catalyst ink, and method for producing the composite of the present invention will be described.
[0011] <Complex> The composite of the embodiment includes molybdenum disulfide particles and palladium particles, and the molybdenum disulfide contained in the molybdenum disulfide particles has an average crystallite size of 150 nm or less, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.
[0012] The composite of the embodiment has a structure in which the molybdenum disulfide particles and the palladium particles are composited together.
[0013] In the present specification, the "composite" may be a state in which molybdenum disulfide particles and palladium particles are integrated by any interaction. The interaction is not particularly limited, but may be a physical interaction between the surface of the molybdenum disulfide particles (for example, if the shape of the molybdenum disulfide particles is sheet-like or ribbon-like (described below), the depressions or wrinkles on the surface are assumed) and the surface of the palladium particles, or a chemical bond such as a coordinate bond, an ionic bond, or an intermolecular force, for example, a bond between S-Pd.
[0014] The average crystallite size of the molybdenum disulfide contained in the molybdenum disulfide particles, as determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement, is 150 nm or less, preferably 50 nm or less, more preferably 40 nm or less, even more preferably 20 nm or less, particularly preferably 10 nm or less, and particularly preferably less than 6 nm. The above peak at 2θ=14.4°±0.5° is attributed to the (002) or (003) plane of molybdenum disulfide (MoS2). If the average crystallite size is small enough to be equal to or smaller than the upper limit value above, the number of catalytically active sites such as interfaces and defects that contribute to catalytic activity increases, improving catalytic performance.
[0015] The lower limit of the average crystallite size of the molybdenum disulfide determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.
[0016] An example of the numerical range of the average crystallite size of the molybdenum disulfide calculated from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be 1 nm or more and 150 nm or less, 2 nm or more and 50 nm or less, 2 nm or more and 40 nm or less, 3 nm or more and 20 nm or less, 3 nm or more and 10 nm or less, or 3 nm or more and less than 6 nm.
[0017] The average crystallite size of the molybdenum disulfide contained in the molybdenum disulfide particles of the embodiment can be determined by the following measurement method.
[0018] [Crystallite size measurement] An X-ray diffraction apparatus (e.g., SmartLab 9kV, manufactured by Rigaku Corporation) is used, a scintillation counter is used as a detector, and analysis software (e.g., PDXL2) is used to perform the measurement. The measurement method is the 2θ / θ method, and the average crystallite size is calculated using the Scherrer equation from the half-width of the peak that appears in the range of 2θ=14.4°±0.5°. The measurement conditions are a scan speed (2θ) of 2.0° / min, a scan range (2θ) of 10 to 70°, a step (2θ) of 0.02°, and no standard width of the apparatus.
[0019] The composite of the embodiment may be a particulate structure (composite particle).
[0020] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 is preferably 1000 nm or less, more preferably 600 nm or less, and even more preferably 500 nm or less. The median diameter D 50 A composite having a molecular weight of 100 or less can more effectively exhibit catalytic efficiency.
[0021] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 For example, it may be 20 nm or more, 40 nm or more, 100 nm or more, or 300 nm or more.
[0022] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 An example of the numerical range of the above numerical value may be 20 nm or more and 1000 nm or less, 40 nm or more and 600 nm or less, 100 nm or more and 500 nm or less, or 300 nm or more and 500 nm or less.
[0023] The median diameter D of the composite of the embodiment calculated by dynamic light scattering method 50 can be determined as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in wet condition using a dynamic light scattering particle size distribution analyzer (e.g., Nanotrac WaveII, manufactured by Microtrack-Bell) with acetone as the medium.
[0024] The specific surface area of the composite of the embodiment measured by the BET method is 10 m 2 / g or more, and 2 / g or more is more preferable, and 2 It is more preferable that the molecular weight is 1 / g or more. A composite having a specific surface area equal to or greater than the above lower limit has a large specific surface area, which increases the number of catalytically active sites and facilitates material transfer in the reaction system, thereby enabling the catalytic efficiency to be improved more effectively.
[0025] The specific surface area of the composite of the embodiment measured by the BET method is, for example, 200 m 2 / g or less, and 2 / g or less.
[0026] An example of the range of the specific surface area of the composite of the embodiment measured by the BET method is 10 m 2 / g or more 200m 2 / g or less, 2 / g or more 200m 2 / g or less, 2 / g or more 100m 2 / g or less.
[0027] The specific surface area is measured using a specific surface area meter (e.g., Microtrack-Bel, BELSORP-mini), and the surface area per 1 g of sample measured from the amount of nitrogen gas adsorbed by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g).
[0028] The ratio of the palladium content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by X-ray fluorescence (XRF) analysis, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more. A composite having a palladium content of at least the above lower limit can more effectively exhibit the catalytic efficiency derived from palladium.
[0029] The ratio of the palladium content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by XRF analysis, may, for example, be 20 mass% or less, 15 mass% or less, or 12 mass% or less.
[0030] An example of the range of the above-mentioned numerical value for the ratio of the palladium content to the total mass (100 mass%) of the composite of the embodiment, as determined by XRF analysis, may be 0.1 mass% or more and 20 mass% or less, 0.5 mass% or more and 15 mass% or less, or 1 mass% or more and 12 mass% or less.
[0031] The ratio of the molybdenum content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by X-ray fluorescence (XRF) analysis, may be 30 mass% or more, 40 mass% or more, or 50 mass% or more.
[0032] The ratio of the molybdenum content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by XRF analysis, may, for example, be 80 mass% or less, 75 mass% or less, or 70 mass% or less.
[0033] An example of the range of the molybdenum content relative to the total mass (100 mass%) of the composite of the embodiment, as determined by XRF analysis, may be 30 mass% or more and 80 mass% or less, 40 mass% or more and 75 mass% or less, or 50 mass% or more and 70 mass% or less.
[0034] The ratio of the sulfur content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by X-ray fluorescence (XRF) analysis, may be 15 mass% or more, 20 mass% or more, or 25 mass% or more.
[0035] The ratio of the sulfur content of the composite of the embodiment relative to the total mass (100 mass%) of the composite, as determined by XRF analysis, may be, for example, 50 mass% or less, 45 mass% or less, or 40 mass% or less.
[0036] An example of the range of the sulfur content relative to the total mass (100 mass%) of the composite of the embodiment, as determined by XRF analysis, may be 15 mass% or more and 50 mass% or less, 20 mass% or more and 45 mass% or less, or 25 mass% or more and 40 mass% or less.
[0037] The molybdenum disulfide particles and the palladium particles will be described in detail below.
[0038] <Molybdenum disulfide particles> The molybdenum disulfide particles contained in the composite of the embodiment are composited with the palladium particles to form the composite.
[0039] The shape of the primary particles of the molybdenum disulfide particle portion in a two-dimensional image obtained by photographing the molybdenum disulfide particles in the composite of the embodiment with a transmission electron microscope (TEM) may be any shape, but is preferably particulate, spherical, plate-like, needle-like, string-like, ribbon-like, or sheet-like, and more preferably string-like, ribbon-like, or sheet-like. The molybdenum disulfide particles may include a combination of these shapes. Here, the term "ribbon-like" or "sheet-like" refers to a thin layer shape, and the term "ribbon-like" refers to a long thin layer shape.
[0040] When the shape of the primary particles of the molybdenum disulfide particle portion is string-like, ribbon-like, or sheet-like, the average thickness measured for the primary particles of 50 molybdenum disulfide particle portions is preferably 100 nm or less, more preferably 50 nm or less, even more preferably 30 nm or less, and particularly preferably 15 nm or less.
[0041] As an example of the numerical range of the thickness, when the shape of the primary particles of the molybdenum disulfide particle portion is string-like, ribbon-like or sheet-like, the average thickness measured for the primary particles of 50 molybdenum disulfide particle portions may be 1 to 100 nm, 3 to 50 nm, 5 to 30 nm, or 5 to 15 nm.
[0042] The shape of the molybdenum disulfide particle portion is preferably a string, ribbon or sheet, and the shape of 50 primary particles of the molybdenum disulfide particle portion is preferably in the range of length (vertical) x width (horizontal) x thickness (height) = 50 to 1000 nm x 50 to 1000 nm x 3 to 100 nm, more preferably in the range of 100 to 500 nm x 100 to 500 nm x 5 to 50 nm, and particularly preferably in the range of 50 to 200 nm x 50 to 200 nm x 5 to 20 nm. By being in the string, ribbon or sheet shape, the specific surface area of the molybdenum disulfide particle portion can be increased. The aspect ratio of the primary particles of the molybdenum disulfide particle portion, i.e., the value of (length (length and width)) / thickness (height)), as an average of 50 particles, is preferably 1.2 to 1200, more preferably 2 to 800, even more preferably 5 to 400, and particularly preferably 10 to 200.
[0043] The length, width, and thickness of the molybdenum disulfide particle portions can be measured with an atomic force microscope (AFM).
[0044] When the shape of the primary particles of the molybdenum disulfide particles is not simple spheres but is string-like, ribbon-like or sheet-like with a large aspect ratio, the specific surface area is increased, and the catalytic efficiency can be effectively improved.
[0045] The molybdenum disulfide particles contain molybdenum disulfide (MoS2). The composite of the embodiment preferably contains 50 mass% or more of molybdenum disulfide (MoS2) relative to the total mass (100 mass%) of the composite, more preferably 80 mass% or more, and even more preferably 85 mass% or more. A composite having a molybdenum disulfide content of at least the above lower limit can more effectively exhibit the catalytic efficiency derived from molybdenum disulfide.
[0046] The upper limit of the content of molybdenum disulfide (MoS2) relative to the total mass (100 mass%) of the composite may be a value such that the sum of the contents of molybdenum disulfide (MoS2), palladium (Pd), and any optional components that may be contained in the composite of the embodiment does not exceed the total mass (100 mass%) of the composite, and may be, for example, 99.9 mass% or less, 99.5 mass% or less, or 99.0 mass% or less.
[0047] The content of molybdenum disulfide (MoS2) may be a value determined by XRF analysis, and can be calculated as the sum of the molybdenum content and the sulfur content determined by XRF analysis of the composite of the embodiment exemplified above.
[0048] As an embodiment, a composite having a palladium content of 0.1% by mass or more and 20% by mass or less and a molybdenum disulfide (MoS2) content of 80% by mass or more and 99.9% by mass or less, relative to the total mass (100% by mass) of the composite, as determined by XRF analysis, can be exemplified. A composite having a palladium content of 0.5% by mass or more and 15% by mass or less and a molybdenum disulfide (MoS2) content of 85% by mass or more and 99.5% by mass or less, and a composite having a palladium content of 1% by mass or more and 12% by mass or less and a molybdenum disulfide (MoS2) content of 88% by mass or more and 99% by mass or less can be exemplified.
[0049] The composite of the embodiment can be provided as an aggregate (for example, powder) of composite particles. If the aggregate contains molybdenum disulfide (MoS), the aggregate can be provided as MoS. x The molybdenum sulfide particles may contain one or more types of molybdenum sulfides represented by (X=1 to 3).
[0050] In addition, the above average crystallite size, D 50 The values relating to the specific surface area and XRF analysis can be values measured using an aggregate of composite particles (eg, powder) as a sample.
[0051] The conversion rate R of the molybdenum disulfide particles to MoS2 C The conversion rate R to MoS2 is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. C When the above lower limit value or more is satisfied, the catalytic performance can be more effectively exhibited.
[0052] Conversion rate of molybdenum disulfide particles to MoS2 R C The RIR value K of molybdenum disulfide (MoS2) can be calculated by the RIR (reference intensity ratio) method from the profile data obtained by measuring molybdenum disulfide particles by X-ray diffraction (XRD). A and the integrated intensity I of the peak at 2θ=14.4°±0.5°, which is assigned to the (002) or (003) plane of molybdenum disulfide (MoS2). A , and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) RIR value K B and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) B Using the above, the conversion rate R to MoS2 is calculated from the following equation (1): C can be sought. R C (%)=(I A / K A ) / (Σ(I B / K B ))×100 (1) Here, the RIR values can be those listed in the Inorganic Crystal Structure Database (ICSD) (manufactured by the Japan Chemical Information Association), and the analysis can be performed using integrated powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation).
[0053] In another aspect, the molybdenum disulfide contained in the molybdenum disulfide particles may include a 3R crystal structure, or may include a 2H crystal structure and a 3R crystal structure. The molybdenum disulfide particles containing such a 2H crystal structure and a 3R crystal structure are uniquely developed by the present applicant, and have not only a 2H crystal structure but also a rare 3R (rhombohedral) structure. Since the 3R structure tends to have a distorted crystal structure and has more catalytically active sites, the inclusion of the 3R crystal structure in molybdenum disulfide contributes to improving catalytic performance.
[0054] The molybdenum disulfide particles containing the 3R crystal structure can be produced, for example, by the <Production method of molybdenum disulfide particles> described below. It is possible to synthesize molybdenum disulfide that contains the 3R structure and is advantageous for achieving a large surface area on the nm scale, which is difficult to achieve by crushing mine products or synthesis from general-purpose molybdenum trioxide.
[0055] The abundance ratio of the 3R crystal structure in the crystal phase of molybdenum disulfide may be 5% or more and 60% or less, 10% or more and 60% or less, 20% or more and 60% or less, or 20% or more and 45% or less.
[0056] The fact that molybdenum disulfide particles have a 2H crystal structure and a 3R crystal structure can be confirmed, for example, by using an extended Rietveld analysis software (High Score Plus, manufactured by Malvern Panalytical) that can take into account the crystallite size. In this Rietveld analysis software, the entire XRD diffraction profile is simulated using a crystal structure model including the crystallite size, and compared with the XRD diffraction profile obtained by experiment, and the crystal lattice constant of the crystal structure model, crystal structure factors such as atomic coordinates, weight fraction (abundance ratio), etc. are optimized by the least squares method so that the residual between the diffraction profile obtained by experiment and the diffraction profile obtained by calculation is minimized, and each phase of the 2H crystal structure and the 3R crystal structure is identified and quantified with high accuracy, and in addition to the crystal structure type and its ratio calculated by normal Rietveld analysis, the crystallite size can be calculated. Hereinafter, in this specification, the analysis method using the above-mentioned High Score Plus is referred to as "Extended Rietveld analysis".
[0057] In addition, in the molybdenum disulfide particles, the crystallite size of the 3R crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD may be 1 nm or more and 150 nm or less, and it is preferable that the particles are made of a crystalline phase composed of crystallites having a size of 5 nm or more and 50 nm or less, and it is more preferable that the crystallite size is 10 nm or more and 40 nm or less.
[0058] Furthermore, in the molybdenum disulfide particles of this embodiment, the crystallite size of the 2H crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD is preferably 1 nm or more and 150 nm or less, and the crystal phase is preferably composed of crystallites having sizes of 1 nm or more and 150 nm or less, and more preferably the crystallite size is 5 nm or more and 150 nm or less.
[0059] The 2H crystal structure obtained by the extended Rietveld analysis is preferably composed of a single crystal phase composed of crystallites having a predetermined crystallite size, and in this case, the crystallite size of the 2H crystal structure is more preferably 1 nm to 20 nm, more preferably 5 nm to 15 nm.
[0060] The crystallite size of the 2H crystal structure and the crystallite size of the 3R crystal structure can also be calculated using, for example, the peak half-width of an XRD diffraction profile.
[0061] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase, which is obtained by extended Rietveld analysis using the profile obtained from the XRD, is preferably 10:90 to 90:10.
[0062] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase, which is obtained by extended Rietveld analysis using the profile obtained from the XRD, is more preferably 10:90 to 80:20, and further preferably 40:60 to 80:20, from the viewpoint of the above-mentioned effects.
[0063] The 2H crystal structure obtained by the extended Rietveld analysis may be composed of a first crystal phase composed of crystallites having a predetermined crystallite size, and a second crystal phase having a smaller crystallite size than the first crystal phase. The crystallite size of the first crystal phase of the 2H crystal structure is, for example, greater than 20 nm and less than 150 nm, and may be 50 nm or more and 150 nm or less, or may be 100 nm or more and 150 nm or less. However, it is preferable that the first crystal phase does not exist in the crystal phase of the 2H crystal structure, or that the abundance ratio of the first crystal phase is low. The crystallite size of the second crystal phase of the 2H crystal structure is preferably 1 nm or more and 20 nm or less, and may be 1 nm or more and 10 nm or less, or may be 5 nm or more and 15 nm or less.
[0064] The crystallite size of the first crystal phase of the 2H crystal structure, the crystallite size of the 3R crystal structure, and the crystallite size of the second crystal phase of the 2H crystal structure can also be calculated using, for example, the half-width of the peaks in the XRD diffraction profile, as described above.
[0065] The abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure in the crystal phase (2H (first crystal phase):3R:2H (second crystal phase)) obtained by extended Rietveld analysis using the profile obtained from the XRD is preferably 30-0:10-70:80-15, and more preferably 25-0:20-60:75-20.
[0066] In a profile obtained by powder X-ray diffraction (XRD) of the molybdenum disulfide particles using Cu-Kα radiation as an X-ray source, the peaks around 2θ=39.5° and 49.5° are derived from the 2H crystal structure, and the peaks around 2θ=32.5°, 39.5°, and 49.5° are derived from the 3R crystal structure, and the half-widths of the peaks around 2θ=39.5° and 49.5° are preferably 1° or more. Furthermore, the molybdenum disulfide particles may contain a crystal structure other than the 2H crystal structure and 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.
[0067] The fact that the molybdenum disulfide particles contain a metastable 3R crystal structure can be distinguished by the fact that in a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, the peaks near 2θ=39.5° and near 2θ=49.5° are both composite peaks of the 2H crystal structure and the 3R crystal structure.
[0068] In practice, the abundance ratio of the 2H crystal structure is determined by the peak near 2θ=39.5° and the broad peak near 49.5° using the profile obtained from the powder X-ray diffraction (XRD). In addition, the abundance ratio of the 3R crystal structure is determined by optimizing the difference between the peak near 2θ=39.5° and the broad peak near 49.5° with two peaks near 2θ=32.5° and two peaks near 39.5°. That is, both the peak near 2θ=39.5° and the peak near 49.5° are composite waves derived from the 2H crystal structure and the 3R crystal structure, and the abundance ratio of the 2H crystal structure and the 3R crystal structure in the molybdenum disulfide particles can be calculated by these composite waves.
[0069] The molybdenum disulfide particles may also contain an amorphous phase. The ratio of the amorphous phase in the molybdenum disulfide particles is expressed as 100(%)-(degree of crystallinity(%)) and is preferably 5% or more, more preferably 15% or more, and even more preferably 20% or more.
[0070] In a radial distribution function obtained from an extended X-ray absorption fine structure (EXAFS) profile of the molybdenum K absorption edge of the molybdenum disulfide particles, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo is preferably greater than 1.0, more preferably 1.1 or more, and particularly preferably 1.2 or more.
[0071] Whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo-S is almost the same due to covalent bonds, so the intensity of the peak due to Mo-S is the same in the extended X-ray absorption fine structure (EXAFS) profile at the K absorption edge of molybdenum. On the other hand, since the 2H crystal structure of molybdenum disulfide is hexagonal, the same hexagon is located 90° directly below the hexagon of the Mo atom, so the distance between Mo-Mo is closer and the peak intensity II due to Mo-Mo is stronger. Conversely, since the 3R crystal structure of molybdenum disulfide is rhombohedral, the hexagon is not directly below the hexagon at 90° but is shifted by half an angle, which increases the distance between Mo-Mo and weakens the peak intensity II due to Mo-Mo. In the pure 2H crystal structure of molybdenum disulfide, the ratio (I / II) is small, but as it contains the 3R crystal structure, the ratio (I / II) becomes larger.
[0072] <Palladium particles> The palladium particles contained in the composite of the embodiment are granular structures containing palladium, and are combined with the molybdenum disulfide particles to form a composite.
[0073] The shape of the palladium particles is not particularly limited, and examples thereof include a sphere, a hemisphere, a wire shape connecting a plurality of palladium particles together, and a shape formed by assembling these shapes.
[0074] The form in which the palladium particles are contained in the composite of the embodiment is not particularly limited, but the palladium particles may be present on the surface of the molybdenum disulfide particles, or may be attached to or bonded to the surface of the molybdenum disulfide particles.
[0075] The number of palladium particles present per 100 nm × 100 nm surface area of the surface of the molybdenum disulfide particle, as confirmed on a two-dimensional image obtained by imaging the composite with a transmission electron microscope (TEM), may be, for example, 5 to 5,000 particles, or 10 to 1,000 particles.
[0076] The average particle size of the palladium particles may be 20 nm or less, 15 nm or less, or 13 nm or less.
[0077] The lower limit of the average particle size of the palladium particles may be, for example, 0.5 nm or more, 0.7 nm or more, or 1 nm or more.
[0078] An example of the range of the average particle size of the palladium particles may be 0.5 nm or more and 20 nm or less, 0.7 nm or more and 15 nm or less, or 1 nm or more and 13 nm or less.
[0079] The average particle size of palladium particles is determined by photographing the complex with a transmission electron microscope (TEM) and measuring the maximum distance between two points on the contour line of 50 randomly selected palladium particles (however, clusters of multiple palladium particles are not selected) from the palladium particles identified in the two-dimensional image. This is the average value.
[0080] The palladium particles contain palladium. The form of palladium contained in the composite of the embodiment is not particularly limited, and for example, the palladium may be contained in the palladium particles as a palladium compound.
[0081] However, as shown in the Examples described later, the following results have been obtained: the XRD pattern of the spectrum obtained by XRD analysis does not show the crystal structure of palladium metal crystals; at least a portion of the palladium constitutes palladium particles, and the palladium particles are observed to be attached to or bonded to the surfaces of molybdenum disulfide particles; no change is observed in the layer spacing that constitutes molybdenum disulfide; and the valence of palladium is zero.
[0082] For these reasons, the palladium particles may contain palladium that does not have a crystal structure. The palladium particles may contain palladium that does not have a crystal structure of palladium metal crystals. The palladium particles may contain palladium that is not in a form in which a part of the molybdenum in the crystal structure of molybdenum disulfide is substituted. The palladium particles may contain zero-valent palladium.
[0083] Regarding the content ratio of palladium in the above-mentioned form, the palladium particles may contain 50% or more of palladium not having a crystal structure on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of palladium not having a crystal structure of palladium metal crystal on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of palladium not in a form substituted with a part of molybdenum in a crystal structure of molybdenum disulfide on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of zero-valent palladium on a molar basis relative to the palladium contained in the palladium particles.
[0084] The palladium particles may include an aggregate of palladium atoms, and may include an aggregate of palladium atoms that does not have a crystal structure. The palladium particles may include an aggregate of palladium atoms that does not have a crystal structure of a palladium metal crystal. The palladium particles may include an aggregate of palladium atoms that is not in a form substituted with a part of the molybdenum in the crystal structure of molybdenum disulfide. The palladium particles may include an aggregate of zero-valent palladium atoms.
[0085] The palladium contained in the palladium particles preferably does not have a crystal structure, and more preferably does not have the crystal structure of palladium metal crystals.
[0086] Similarly, the complex of the embodiment may include palladium that does not have a crystal structure. The complex of the embodiment may include palladium that does not have the crystal structure of a palladium metal crystal. The complex of the embodiment may include palladium that is not in a form in which a portion of the molybdenum in the crystal structure of molybdenum disulfide is substituted. The complex of the embodiment may include palladium with a valence of zero.
[0087] Regarding the content ratio of palladium in the above-mentioned form of inclusion, the composite of the embodiment may contain 50% or more of palladium not having a crystal structure on a molar basis relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium not having a crystal structure of palladium metal crystal on a molar basis relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium not in a form substituted with a part of molybdenum in the crystal structure of molybdenum disulfide on a molar basis relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium with a valence of zero on a molar basis relative to the palladium contained in the composite.
[0088] Similarly, the complex of the embodiment may include an aggregate of palladium atoms that does not have a crystal structure. The complex of the embodiment may include an aggregate of palladium atoms that does not have the crystal structure of a palladium metal crystal. The complex of the embodiment may include an aggregate of palladium atoms that is not in a form substituted with a portion of the molybdenum in the crystal structure of molybdenum disulfide. The complex of the embodiment may include an aggregate of palladium atoms with a valence of 0.
[0089] The palladium contained in the composite of the embodiment preferably does not have a crystal structure, and more preferably does not have the crystal structure of a palladium metal crystal.
[0090] In another aspect, the composite of the embodiment includes molybdenum disulfide particles and palladium particles, and the molybdenum disulfide contained in the molybdenum disulfide particles has an average crystallite size of 150 nm or less, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement (excluding composites in which the palladium contained in the composite has a crystal structure of palladium metal crystals).
[0091] The palladium in the composite of the embodiment may form palladium clusters. Also, the palladium in the palladium particles may form palladium clusters.
[0092] The presence of a crystal structure containing palladium can be detected based on a diffraction profile obtained by X-ray diffraction analysis of the composite of the embodiment as a sample, or based on analysis of the crystal structure by electron beam diffraction.
[0093] According to the composite of the embodiment described above, the molybdenum disulfide particles having a fine crystallite size, such as the average crystallite size of 150 nm or less, and the palladium particles are composited together, and thus the composite can exhibit excellent catalytic performance.
[0094] Furthermore, it is believed that even better catalytic performance can be achieved by the palladium in the above palladium particles not forming a crystal structure of palladium metal crystals, but preferably being present in the molybdenum disulfide particles as an aggregate of palladium (Pd) atoms.
[0095] The composite of the embodiment can be used as a catalyst, and in particular, can be suitably used as a hydrogen generation catalyst applied to water electrolysis and the like. Furthermore, the composite of the embodiment can be suitably used as a constituent material of a catalyst ink capable of forming a catalyst layer. Moreover, the composite of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0096] <Method for manufacturing the composite> A method for producing a composite according to an embodiment includes a step of mixing molybdenum disulfide particles with a palladium solution, and the molybdenum disulfide contained in the molybdenum disulfide particles has an average crystallite size of 150 nm or less, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.
[0097] According to the method for producing a composite of the embodiment, it is possible to produce the composite of the above embodiment.
[0098] Examples of the molybdenum disulfide particles include those exemplified in the above "composite".
[0099] The palladium solution can be obtained by dissolving any palladium source in a solvent.
[0100] The palladium source may be any source capable of producing a palladium solution, and examples thereof include palladium compounds such as palladium acetate, palladium nitrate, palladium nitrite, palladium sulfate, palladium carbonate, palladium chloride, palladium hydroxide, and palladium oxide.
[0101] The solvent may be any solvent capable of dissolving the palladium source, and examples of the solvent include alcohols such as methanol, benzene, dichloromethane, acetone, and chloroform.
[0102] The method of mixing is not particularly limited, but it is preferable to mix a palladium solution with a dispersion of molybdenum disulfide particles.
[0103] The dispersion of molybdenum disulfide particles can be obtained by mixing the solvent exemplified for the palladium solution above with molybdenum disulfide particles.
[0104] A composite of molybdenum disulfide particles and palladium particles can be formed by mixing a palladium solution with molybdenum disulfide particles to obtain a mixture and then contacting the molybdenum disulfide particles with the palladium solution.
[0105] From the viewpoint of preventing aggregation of the molybdenum disulfide particles, for example, it is preferable to stir the mixture of the palladium solution and the molybdenum disulfide particles, and the stirring speed can be, for example, 50 to 1000 rpm.
[0106] The concentration of palladium in the palladium solution may be, for example, 0.00001 to 0.1 mol / L, or 0.0001 to 0.01 mol / L.
[0107] The temperature of the mixture of the molybdenum disulfide particles and the palladium solution may be at a level that allows the formation of a composite, and may be, for example, 10 to 100°C, or 20 to 80°C.
[0108] The retention time of the mixture of molybdenum disulfide particles and palladium solution may be long enough to form a complex, and may be, for example, from 10 minutes to 48 hours, or from 30 minutes to 12 hours.
[0109] In the method for producing a composite according to the embodiment, the mixture of molybdenum disulfide particles and palladium solution may be irradiated with light in order to promote the photoreduction of palladium. The light irradiation may be performed by appropriately selecting the amount of light and wavelength to an extent that the photoreduction of palladium occurs. The light irradiation may be performed by installing a light source to control the light intensity, or may be performed by irradiating with light in a normal indoor environment (by lighting such as fluorescent lamps or LEDs) or natural light.
[0110] In the manufacturing method of molybdenum disulfide described below, a heating operation is included in the manufacturing process. However, in the manufacturing method of the composite of the embodiment, the composite can be manufactured without performing a heat treatment. For example, the obtained composite or the mixture of the palladium solution and the molybdenum disulfide particles is preferably not heated to 200°C or higher, more preferably not heated to more than 100°C, and even more preferably not heated to more than 80°C.
[0111] After the complex is formed from the mixture, the complex can be separated by a process such as centrifugation or drying, and the complex of the embodiment can be easily recovered.
[0112] The method for producing a composite according to the embodiment may further include a step of producing the molybdenum disulfide particles.
[0113] An example of a method for producing molybdenum disulfide particles will now be described.
[0114] <Method of manufacturing molybdenum disulfide particles> The molybdenum disulfide particles can be produced, for example, by a molybdenum disulfide particle production process including heating molybdenum trioxide particles having an average primary particle size of 2 nm or more and 1000 nm or less at a temperature of 200 to 1000° C. in the presence of a sulfur source.
[0115] In another aspect, the molybdenum disulfide particles can be produced, for example, by a molybdenum disulfide particle production process including heating molybdenum trioxide particles obtained by a molybdenum trioxide particle production process described below, in the presence of a sulfur source, at a temperature of 200 to 1000°C.
[0116] The average particle size of the primary particles of molybdenum trioxide particles refers to the average value of primary particle diameters of 50 randomly selected primary particles when molybdenum trioxide particles are photographed with a scanning electron microscope (SEM) or transmission electron microscope (TEM), and the long axis (the Feret diameter of the longest observed part) and short axis (the shorter Feret diameter perpendicular to the Feret diameter of the longest part) of the smallest unit particle (i.e., primary particle) that constitutes the aggregate in the two-dimensional image are measured, and the average value is taken as the primary particle diameter.
[0117] In the method for producing molybdenum disulfide particles, the molybdenum trioxide particles preferably have an average particle size of 1 μm or less. From the viewpoint of reactivity with sulfur, the average particle size of the molybdenum trioxide particles is more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. The average particle size of the molybdenum trioxide particles may be 2 nm or more, 5 nm or more, or 10 nm or more.
[0118] The molybdenum trioxide particles used in the production of the molybdenum disulfide particles are preferably composed of an aggregate of primary particles containing the β crystal structure of molybdenum trioxide. The molybdenum trioxide particles have a better reactivity with sulfur than conventional molybdenum trioxide particles consisting only of α crystals as a crystal structure, and because they contain the β crystal structure of molybdenum trioxide, the conversion rate R to MoS2 in the reaction with a sulfur source is higher. C can be made larger.
[0119] The β-crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database (ICSD))) that belongs to the (011) plane of the β-crystal of MoO3 in the profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as the X-ray source. The α-crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database (ICSD)))) that belongs to the (021) plane of the α-crystal of MoO3.
[0120] In a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, the molybdenum trioxide particles preferably have a ratio (β(011) / α(021)) of the peak intensity attributable to the (011) plane of a β crystal of MoO3 to the peak intensity attributable to the (021) plane of an α crystal of MoO3 (2θ: near 27.32°_No. 166363 (Inorganic Crystal Structure Database (ICSD))) of 0.1 or more.
[0121] For the peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3, the maximum peak intensity is read and the ratio (β(011) / α(021)) is calculated.
[0122] In the molybdenum trioxide particles, the ratio (β(011) / α(021)) is preferably from 0.1 to 10.0, more preferably from 0.2 to 10.0, and particularly preferably from 0.4 to 10.0.
[0123] The β crystal structure of molybdenum trioxide is observed at wavenumbers of 773 and 848 cm in the Raman spectrum obtained by Raman spectroscopy. -1 and 905 cm -1 The α-crystal structure of molybdenum trioxide can also be confirmed by the presence of peaks at wavenumbers 663 and 816 cm. -1 and 991 cm -1 This can be confirmed by the presence of a peak at
[0124] The molybdenum trioxide particles may have an average primary particle size of 5 nm or more and 2000 nm or less.
[0125] Examples of the sulfur source include sulfur and hydrogen sulfide, which may be used alone or in combination.
[0126] The method for producing molybdenum disulfide particles may include heating molybdenum trioxide particles consisting of an aggregate of primary particles containing a β crystal structure of molybdenum trioxide at a temperature of 100 to 800°C in the absence of a sulfur source, and then heating it at a temperature of 200 to 1000°C in the presence of a sulfur source.
[0127] The heating time in the presence of the sulfur source may be any time that allows the sulfurization reaction to proceed sufficiently, and may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours.
[0128] In the method for producing molybdenum disulfide particles, the ratio of the amount of S in the sulfur source to the amount of MoO3 in the molybdenum trioxide particles is preferably set under conditions that allow the sulfurization reaction to proceed sufficiently. The amount of S in the sulfur source is preferably 450 mol% or more, more preferably 600 mol% or more, and even more preferably 700 mol% or more, relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide particles. The amount of S in the sulfur source may be 3000 mol% or less, 2000 mol% or less, or 1500 mol% or less, relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide particles.
[0129] In the method for producing molybdenum disulfide particles, the heating temperature in the presence of the sulfur source may be any temperature at which the sulfurization reaction proceeds sufficiently, and is preferably 320° C. or higher, more preferably 340° C. or higher, and even more preferably 360° C. or higher. The heating temperature may be 320 to 1000° C., 340 to 1000° C., or 360 to 500° C. By lowering the heating temperature, the crystallinity of the molybdenum disulfide particles decreases, and the proportion of the amorphous phase can be increased.
[0130] In the method for producing molybdenum disulfide particles, the obtained molybdenum disulfide particles may be cooled and then heated as a post-treatment, if necessary. In this heat treatment, it is preferable to sinter the molybdenum disulfide particles, for example, under an inert atmosphere. By heating and sintering the obtained molybdenum disulfide particles, crystallization of the amorphous phase is promoted, and the degree of crystallization is improved. In addition, with the improvement in the degree of crystallization, new 2H crystal structures and 3R crystal structures are generated, and the abundance ratio of the 2H crystal structure and the 3R crystal structure changes. In this way, reheating as a post-treatment can improve the abundance ratio of the 3R crystal structure. In addition, the abundance ratio of the 2H crystal structure and the 3R crystal structure can be adjusted by changing the temperature at which the obtained molybdenum disulfide particles are heated.
[0131] When the amorphous phase is converted to a 2H crystal structure by heating and sintering the obtained molybdenum disulfide particles at a predetermined temperature or higher, a second crystal phase composed of crystallites with a crystallite size of 20 nm or less, preferably 10 nm or less, is newly generated. In this case, if there are crystallites with a crystallite size of 10 nm or less in the 2H crystal structure before the molybdenum disulfide particles are heated, the crystallites grow to a crystallite size of 100 nm or more after the molybdenum disulfide particles are heated, and a first crystal phase composed of the grown crystallites is generated.
[0132] From the viewpoint of increasing the abundance ratio of the crystal phase having the 3R crystal structure while decreasing the abundance ratio of the first crystal phase having the 2H crystal structure as much as possible, the heating temperature of the molybdenum disulfide particles in the post-treatment is preferably 500 to 900°C, and more preferably 500 to 800°C.
[0133] The heating rate of the molybdenum disulfide particles in the post-treatment is preferably 1° C. / min or more and 50° C. / min or less, and more preferably 2° C. / min or more and 10° C. / min or less.
[0134] In the method for producing the molybdenum disulfide particles, the molybdenum trioxide particles preferably have a MoO3 content of 99.5% or more as measured by X-ray fluorescence (XRF). C It is possible to obtain high-purity molybdenum disulfide that is free from the risk of producing disulfides derived from impurities and has good storage stability.
[0135] The molybdenum trioxide particles have a specific surface area of 10 m as measured by the BET method. 2 / g~100m 2 It is preferred that the molecular weight is / g.
[0136] In the molybdenum trioxide particles, the specific surface area is 10 m because the reactivity with sulfur is good. 2 / g or more, and 2 / g or more is more preferable, and 30m2 In the molybdenum trioxide particles, the particle size is preferably 100 m 2 / g or less, and 2 / g or less, 2 / g or less.
[0137] The molybdenum trioxide particles have a peak intensity I due to Mo-O and a peak intensity II due to Mo-Mo in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) profile at the K absorption edge of molybdenum. O Ratio to (I O / II O ) is preferably greater than 1.1.
[0138] Intensity of the peak due to Mo-O I O , and Mo-Mo peak intensity II O The maximum intensity of the peaks was read, and the ratio (I O / II O ) is calculated. O / II O ) is considered to be a measure of whether the β crystal structure of MoO3 is obtained in the molybdenum trioxide particles, and the above ratio (I O / II O ) is larger, the reactivity with sulfur is higher.
[0139] In the molybdenum trioxide particles, the ratio (I O / II O ) is preferably from 1.1 to 5.0, may be from 1.2 to 4.0, or may be from 1.2 to 3.0.
[0140] (Method of producing molybdenum trioxide particles) The method for producing the composite according to the embodiment may further include a molybdenum trioxide production step of producing the molybdenum trioxide particles.
[0141] The molybdenum trioxide particles may be produced by a molybdenum trioxide manufacturing process that includes vaporizing a molybdenum oxide precursor compound to form molybdenum trioxide vapor and cooling the molybdenum trioxide vapor.
[0142] The method for producing molybdenum trioxide particles includes calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, and vaporizing the molybdenum oxide precursor compound to form molybdenum trioxide vapor, and it is preferable that the proportion of the metal compound relative to 100 mass% of the raw material mixture is 70 mass% or less, calculated as oxide.
[0143] The method for producing the molybdenum trioxide particles can be suitably carried out using a production apparatus 1 shown in FIG.
[0144] FIG. 1 is a schematic diagram showing an example of an apparatus used for producing molybdenum trioxide particles, which are a raw material for the molybdenum disulfide particles according to this embodiment. As shown in FIG. 1, the manufacturing apparatus 1 includes a calcination furnace 2 for calcining a molybdenum trioxide precursor compound or the raw material mixture and vaporizing the molybdenum trioxide precursor compound, a cross-shaped cooling pipe 3 connected to the calcination furnace 2 for granulating the molybdenum trioxide vapor vaporized by the calcination, and a recovery device 4 as a recovery means for recovering the molybdenum trioxide particles granulated by the cooling pipe 3. At this time, the calcination furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 has an opening adjustment damper 6 at the left end of an outside air intake port (not shown) and an observation window 7 at the upper end. The recovery device 4 is connected to an exhaust device 8 as a first blowing means. When the exhaust device 8 exhausts air, the internal gas of the recovery device 4 and the cooling pipe 3 is sucked in, and outside air is blown into the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 performs a suction function, and thus air is passively blown to the cooling pipe 3. The production apparatus 1 may have an external cooling device 9, which makes it possible to arbitrarily control the cooling conditions for the molybdenum trioxide vapor generated from the firing furnace 2.
[0145] By opening the opening adjustment damper 6, air is taken in from the outside air intake port, and the molybdenum trioxide vapor vaporized in the baking furnace 2 is cooled in the air atmosphere and turned into molybdenum trioxide particles, thereby achieving the ratio (I O / II O ) can be made larger than 1.1, and the β crystal structure of MoO3 can be easily obtained in the molybdenum trioxide particles. When the molybdenum trioxide vapor is cooled using liquid nitrogen or the like in a nitrogen atmosphere with a low oxygen concentration, the oxygen vacancy density is increased, and the ratio (I O / II O ) is easily reduced.
[0146] The molybdenum oxide precursor compound is not particularly limited as long as it can form molybdenum trioxide vapor by firing it. Examples of the molybdenum oxide precursor compound include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (HPMo 12 O40 ), silicomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n=1-3)), sodium molybdate (Na2Mo n O 3n+1 (n=1-3)), titanium molybdate, iron molybdate, potassium molybdate (KMo n O 3n+1 (n=1~3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1 (n=1 to 3), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds may be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, and may be, for example, a powder such as molybdenum trioxide, or a liquid such as an aqueous solution of ammonium molybdate, but is preferably a powder that is easy to handle and has good energy efficiency.
[0147] It is particularly preferable to use commercially available α-crystalline molybdenum trioxide as the molybdenum trioxide precursor compound. When ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted to thermodynamically stable molybdenum trioxide by calcination, and the vaporized molybdenum oxide precursor compound becomes the molybdenum trioxide.
[0148] Molybdenum trioxide vapor can also be produced by firing a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0149] Of these, the molybdenum oxide precursor compound preferably contains molybdenum trioxide, in terms of ease of control of the purity, average primary particle size, and crystal structure of the resulting molybdenum trioxide powder.
[0150] There are cases where an intermediate is generated between a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound. Even in this case, the intermediate is decomposed by firing, and molybdenum trioxide can be vaporized in a thermodynamically stable form.
[0151] As the metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound among these in order to prevent damage to the firing furnace, and it is also possible not to use a metal compound other than the molybdenum oxide precursor compound in order to improve the purity of the molybdenum trioxide particles.
[0152] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, it is preferable to use the aluminum compounds, silicon compounds, titanium compounds, or magnesium compounds as the metal compound.
[0153] There are cases where an intermediate is generated between a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound. Even in this case, the intermediate is decomposed by calcination, and molybdenum trioxide can be vaporized in a thermodynamically stable form.
[0154] As the metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound in order to prevent damage to a firing furnace. In the production method, it is not necessary to use a metal compound other than the molybdenum oxide precursor compound in order to improve the purity of the molybdenum trioxide powder.
[0155] Examples of aluminum compounds include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition aluminum oxides (such as γ-aluminum oxide, δ-aluminum oxide, and θ-aluminum oxide), α-aluminum oxide, and mixed aluminum oxides having two or more crystal phases.
[0156] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is fired, the content of the molybdenum oxide precursor compound relative to 100 mass% of the raw material mixture is preferably 40 mass% or more and 100 mass% or less, may be 45 mass% or more and 100 mass% or less, or may be 50 mass% or more and 100 mass% or less.
[0157] The calcination temperature varies depending on the molybdenum oxide precursor compound, metal compound, desired molybdenum trioxide particles, etc., but is usually preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate may be formed as an intermediate, so the calcination temperature is preferably 500 to 1500°C, more preferably 600 to 1550°C, and even more preferably 700 to 1600°C.
[0158] The firing time is not particularly limited, but may be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.
[0159] The heating rate varies depending on the molybdenum oxide precursor compound and the metal compound used, and the properties of the desired molybdenum trioxide particles, but from the viewpoint of production efficiency, the heating rate is preferably 0.1°C / min to 100°C / min, more preferably 1°C / min to 50°C / min, and even more preferably 2°C / min to 10°C / min.
[0160] The internal pressure in the calcination furnace is not particularly limited and may be positive pressure or reduced pressure, but from the viewpoint of suitably discharging the molybdenum oxide precursor compound from the calcination furnace to a cooling pipe, it is preferable to carry out the calcination under reduced pressure. A specific degree of reduced pressure is preferably -5000 Pa to -10 Pa, more preferably -2000 Pa to -20 Pa, and even more preferably -1000 Pa to -50 Pa. A degree of reduced pressure of -5000 Pa or more is preferable because it does not require excessive airtightness or mechanical strength of the calcination furnace, and it is possible to reduce the manufacturing cost. On the other hand, a degree of reduced pressure of -10 Pa or less is preferable because it is possible to prevent clogging of the molybdenum oxide precursor compound at the exhaust port of the calcination furnace.
[0161] When gas is blown into the firing furnace during firing, the temperature of the gas blown is preferably 5 to 500°C, and more preferably 10 to 100°C.
[0162] The gas blowing speed is preferably 1 L / min to 500 L / min, and more preferably 10 L / min to 200 L / min, relative to the effective volume of the firing furnace of 100 L.
[0163] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200 to 2000° C., and more preferably 400 to 1500° C. When the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or lower, it usually tends to be easily granulated in a cooling pipe by blowing outside air (0 to 100° C.).
[0164] The discharge rate of molybdenum trioxide vapor discharged from the calcination furnace can be controlled by the amount of the molybdenum oxide precursor compound and the amount of the metal compound used, the temperature of the calcination furnace, the gas blown into the calcination furnace, and the diameter of the calcination furnace exhaust port. Although it varies depending on the cooling capacity of the cooling piping, the discharge rate of molybdenum trioxide vapor from the calcination furnace to the cooling piping is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.
[0165] The content of molybdenum trioxide vapor contained in the gas discharged from the calciner is preferably 0.01 mg / L or more and 1000 mg / L or less, and more preferably 1 mg / L or more and 500 mg / L or less.
[0166] The molybdenum trioxide vapor is then cooled and granulated. The molybdenum trioxide vapor is cooled by lowering the temperature of the cooling pipe. In this case, the cooling means may be, as described above, cooling by blowing gas into the cooling pipe, cooling by a cooling mechanism of the cooling pipe, or cooling by an external cooling device.
[0167] The molybdenum trioxide vapor is preferably cooled in an air atmosphere. By cooling the molybdenum trioxide vapor in an air atmosphere to form molybdenum trioxide particles, the ratio (I O / II O ) can be made larger than 1.1, and the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide particles.
[0168] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably from -100 to 600°C, and more preferably from -50 to 400°C.
[0169] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably from 100° C. / s to 100,000° C. / s, and more preferably from 1,000° C. / s to 50,000° C. / s. Note that the faster the cooling rate of the molybdenum trioxide vapor, the smaller the particle size and the larger the specific surface area of the molybdenum trioxide particles that are obtained tend to be.
[0170] When the cooling means is a means for cooling by blowing gas into a cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, and more preferably -50 to 100°C.
[0171] The gas flow rate is 0.1 m 3 / min or more 20m 3 / min or less is preferable, and 3 / min or more 10m 3 It is more preferable that the gas blowing speed is 0.1 m / min or less. 3 / min or more, a high cooling rate can be realized and clogging of the cooling pipes can be prevented, which is preferable. 3 / min or less is preferable because it eliminates the need for expensive first blowing means (exhaust fan, etc.), thereby enabling the manufacturing cost to be reduced.
[0172] The molybdenum trioxide vapor is cooled and the resulting particles are transported to a collector for recovery.
[0173] In the method for producing molybdenum trioxide particles, the molybdenum trioxide vapor may be cooled to obtain particles, which may be calcined again at a temperature of 100 to 320°C.
[0174] That is, the molybdenum trioxide particles obtained by the method for producing molybdenum trioxide particles may be calcined again at a temperature of 100 to 320°C. The calcination temperature of the second calcination may be 120 to 280°C, or 140 to 240°C. The calcination time of the second calcination may be, for example, 1 minute to 4 hours, 10 minutes to 5 hours, or 100 minutes to 6 hours. However, by calcining again, a part of the β crystal structure of molybdenum trioxide is lost, and when calcined at a temperature of 350°C or higher for 4 hours, the β crystal structure in the molybdenum trioxide particles is lost, the ratio (β(011) / α(021)) becomes 0, and the reactivity with sulfur is impaired. By the method for producing molybdenum trioxide particles described above, it is possible to produce molybdenum trioxide particles suitable for producing the molybdenum disulfide particles.
[0175] <Hydrogen generation catalyst> The composite of the embodiment can be suitably used as a catalyst in the hydrogen generation reaction (HER) (sometimes referred to as "hydrogen generation catalyst" in this specification). The composite of the embodiment can also be used as a hydrogen generation catalyst when used in combination with a conductive material. That is, a preferred hydrogen generation catalyst is, for example, one that contains the composite of the embodiment, and the hydrogen generation catalyst may further contain a conductive material in addition to the composite of the embodiment. The catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) that contains the composite of the embodiment and a conductive material is higher.
[0176] The conductive material may be any known material. Examples of the conductive material include carbon and metals, which have high conductivity. The hydrogen generation catalyst may contain only one type of conductive material, or may contain two or more types of conductive materials.
[0177] Examples of the conductive material include carbon black such as acetylene black, Cabot carbon black, and Ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and electrical conductivity, and is also excellent in that it can suppress the aggregation of molybdenum sulfide.
[0178] Examples of the metal that is the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium. The metal as the conductive material is different from the palladium in the composite of the embodiment, and in the hydrogen generation catalyst, it is merely mixed with the composite of the embodiment.
[0179] The hydrogen generation catalyst may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0180] The hydrogen generation catalyst may, for example, contain no metal but contain carbon as a conductive material, may contain no carbon but contain a metal, or may contain both a metal and carbon.
[0181] In the hydrogen generation catalyst, the content of the conductive material is preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 50 parts by mass, relative to 100 parts by mass of the content of the composite of the embodiment.
[0182] In the hydrogen generation catalyst, the ratio of the total content of the composite of the embodiment and the conductive material to the total mass (100 mass%) of the hydrogen generation catalyst is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, and may be, for example, any of 97 mass% or more and 99 mass% or more, or may be 100 mass%. When the ratio is equal to or more than the lower limit, the catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) becomes higher. The ratio may be 100 mass% or less.
[0183] <Catalyst ink> The hydrogen generating catalyst is suitable as a component contained in a catalyst ink. The catalyst ink of the embodiment contains the complex of the embodiment and a solvent. The catalyst ink of the embodiment may contain the composite of the embodiment, a polymer electrolyte, and a solvent.
[0184] The catalyst ink of this embodiment may further contain a conductive material. The type and content of the conductive material may be those exemplified above.
[0185] The catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0186] The polymer electrolyte may be one generally used in the formation of a catalyst layer.Specific examples of the polymer electrolyte include perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton-conductive functional groups, and proton conductors in which a polymer matrix is impregnated with a phosphoric acid solution or a sulfuric acid solution.
[0187] Examples of the solvent include a solvent capable of dispersing the composite of the embodiment and capable of forming a catalyst layer by applying the solvent to a working electrode substrate, etc. The solvent preferably contains an alcohol such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, or 2-heptanol. EXAMPLES
[0188] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0189] [Synthesis Example 1] (Reference Example) (Production of molybdenum trioxide particles) A calcination furnace equivalent to a heat-resistant container, a cooling pipe with an external air supply port, and a dust collector for collecting molybdenum oxide were prepared. Molybdenum oxide was produced using an RHK simulator (manufactured by Noritake Co., Ltd.) as the calcination furnace and a VF-5N dust collector (manufactured by Amano Corporation) as the dust collector. 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Muki Co., Ltd.) were mixed and then charged into a sagger. The firing furnace was connected to a cooling pipe and a dust collector, and the mixture was fired at a temperature of 1100°C for 10 hours. During firing, outside air (air flow rate: 150 L / min, outside air temperature: 25°C) was introduced from the side and bottom of the firing furnace. After evaporating in the furnace, molybdenum trioxide was cooled near the dust collector and precipitated as particles, and the molybdenum trioxide was collected by the dust collector. After calcination, 1.0 kg of blue powder aluminum oxide was taken out from the scabbard and 0.8 kg of molybdenum trioxide was collected in a dust collector. The recovered molybdenum trioxide had a primary particle size of 1 μm or less, and fluorescent X-ray measurement confirmed that the purity of the molybdenum trioxide was 99.8%.
[0190] (Production of molybdenum disulfide particles) Into an alumina crucible, 40.0 g (277.9 mmol) of the molybdenum trioxide prepared above and 40.0 g (1250 mmol, 4.5 equivalents to Mo atoms) of sulfur powder (manufactured by Kanto Chemical Co., Ltd.) were added, and mixed with a stirring rod so that the powders were uniform. After mixing, the alumina crucible was covered with a lid and placed in a high-temperature atmosphere firing furnace (manufactured by Motoyama Co., Ltd., SKM-2030P-OP), and the inside of the furnace was evacuated and replaced with nitrogen, and then firing was performed. The firing conditions were as follows: the temperature was raised from room temperature of 25°C at a rate of 5°C / min, and after reaching 500°C, the temperature was maintained for 4 hours. During the firing process, nitrogen gas was blown at 0.5 L / min. After that, the temperature inside the furnace was lowered by natural cooling, and 44.5 g of molybdenum disulfide particles were obtained.
[0191] (Production of the complex) [Example 1] 100 mg of the molybdenum disulfide particles obtained in Synthesis Example 1 above were mixed with 25 mL of methanol (Kanto Chemical Co., Ltd. reagent, CH3OH) and subjected to ultrasonic treatment for 30 minutes to obtain a dispersion in which the molybdenum disulfide particles were dispersed in methanol. Palladium acetate (Kanto Chemical Co., Ltd., reagent, Pd(CH3COO)2) 4.3 mg was mixed with 25 mL of methanol to dissolve the palladium acetate in methanol, and the resulting solution was added to the above dispersion liquid in a stirred state. The mixture was then stirred at room temperature under light irradiation (normal indoor bright environment) for 2 hours or more to obtain a precipitate. The precipitate was collected using a centrifuge, ultrasonically washed three times in water, and then vacuum dried to obtain the composite particles of Example 1.
[0192] [Examples 2 to 4] Each of the composite particles of Examples 2 to 4 was obtained in the same manner as in Example 1 above, except that the amounts of palladium acetate and methanol used in Example 1 (half the amounts of methanol shown in the table were used for the dispersion of molybdenum disulfide particles and the palladium solution) were changed as shown in Table 1.
[0193] [Comparative Example 1] In Example 2, instead of 100 mg of the molybdenum disulfide particles obtained in Synthesis Example 1, commercially available carbon black (KB) (Ketjen Black, product number: EC300J, manufactured by Lion Specialty Chemicals Co., Ltd., median diameter D 50 Particles of Comparative Example 1 were obtained in the same manner as in Example 2 above, except that 100 mg of the nanoparticles (particle size: 40 nm) were used.
[0194] [Comparative Example 2] Commercially available molybdenum disulfide particles (manufactured by Kanto Chemical Co., Ltd.) were used as the particles of Comparative Example 2.
[0195] The particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 and 2 were used as samples and evaluated as follows.
[0196] Evaluation [XRF analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 20-30 mg of the sample was placed on filter paper and covered with a PP film for composition analysis. The amounts of palladium, molybdenum, and sulfur obtained from the XRF analysis results were calculated as the palladium content (mass%), molybdenum content (mass%), and sulfur content (mass%) relative to 100% mass of the sample particles.
[0197] [XRD crystal structure measurement] The sample was loaded into a measurement sample holder with a depth of 0.5 mm and set in a wide-angle X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation). Measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2θ = 2° / min, and scan range 2θ = 10° to 70°.
[0198] [Crystallite size measurement] The measurement was performed using a SmartLab 9kV (Rigaku Corporation) as an X-ray diffraction device, a scintillation counter detector as a detector, and PDXL2 as analysis software. The measurement method was the 2θ / θ method, and the average crystallite size was calculated using the Scherrer formula from the half-width of the peak appearing at 2θ=14.4°±0.5°. The measurement conditions were a scan speed (2θ) of 2.0° / min, a scan range (2θ) of 10-70°, a step (2θ) of 0.02°, and no standard width of the device.
[0199] [XPS analysis] The prepared sample was fixed onto carbon tape and subjected to composition analysis using an X-ray photoelectron spectroscopy (XPS) device (K-Alpha, manufactured by ThermoFisher Scientific, Japan) under the following conditions. X-ray source: Monochrome AlKα, 12kV, 6mA Measurement diameter: 400μm Static charge compensation: None X-ray take-off angle: 90°
[0200] [Measurement of BET specific surface area] The specific surface area was measured using a specific surface area meter (Microtrack-Bel, BELSORP-mini), and the surface area per gram of sample measured from the amount of nitrogen gas adsorbed by the BET method was calculated as the specific surface area.
[0201] [Median diameter D 50 Measurement of 0.1 g of sample powder was added to 20 cc of acetone, and ultrasonicated in an ice bath for 4 hours. The concentration was then adjusted with acetone to a suitable range within the measurable range of a dynamic light scattering particle size distribution analyzer (Microtrack Bell, Nanotrac WaveII) to obtain a measurement sample. Using this measurement sample, the particle size distribution in the particle size range of 0.0001 μm to 10 μm was measured with the dynamic light scattering particle size distribution analyzer, and the median diameter D 50 The median diameter D 50 For those having a particle diameter of more than 10 μm (Comparative Example 2), a solution was prepared in the same manner, and the particle diameter distribution in the particle diameter range of 0.015 μm to 500 μm was measured using a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7000). 50 was calculated.
[0202] [Measurement of the average particle size of palladium particles] The sample powder was photographed with a high-resolution transmission electron microscope (HR-TEM, JEM-ARM300F, manufactured by JEOL Ltd.), and the palladium particles confirmed in the two-dimensional image were analyzed. The average of the maximum distances between two points on the contour line of 50 randomly selected palladium particles (however, aggregates of multiple palladium particles were not selected) was used as the average particle size of the palladium particles.
[0203] The results of the above measurements are shown in Table 1.
[0204] [Table 1]
[0205] The particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 to 2 have the palladium content, molybdenum content, sulfur content, MoS2 content, MoS2 average crystallite size, average particle size of palladium particles, BET specific surface area, and D 50 had the following characteristics:
[0206] The results of the XRD analysis are shown in Figure 2. The XRD profiles of the composite particles of Examples 1 to 4 were almost identical to the XRD profile of the molybdenum disulfide particles of Synthesis Example 1. On the other hand, the XRD profile of the particles using carbon black of Comparative Example 1 was almost identical to the XRD profile of standard palladium (Pd).
[0207] FIG. 3 shows images of the particles of Synthesis Example 1, Examples 1 to 4, and Comparative Example 1 observed with a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400). In the TEM images shown here, it is clear from Examples 3 to 4 and Comparative Example 1 that spherical particles with diameters of about 1 to 10 nm are observed adhering to or bonded to molybdenum disulfide particles or carbon black particles.
[0208] FIG. 4 shows an image of the composite particle of Example 2 observed with a high-resolution transmission electron microscope (HR-TEM, JEM-ARM300F, manufactured by JEOL Ltd.) and the results of element mapping by energy dispersive X-ray spectroscopy (EDS). From the elemental mapping results, a high density of Pd was detected at the position corresponding to the above-mentioned spherical particles. From this, it was determined that the above-mentioned spherical particles with a diameter of about 1 to 10 nm observed by TEM correspond to palladium particles containing Pd.
[0209] In the composite particles of Examples 1 to 4, the diffraction patterns derived from the crystal structure of palladium metal were not confirmed in the above XRD analysis. This indicates that the Pd in the composite particles of Examples 1 to 4 does not have the crystal structure of palladium metal crystals.
[0210] Furthermore, the angle values of the peak (peak top) appearing at 2θ=14.4±0.5° in the above XRD analysis were 14.20° for Synthesis Example 1, 14.20° for Example 1, 14.20° for Example 2, 14.20° for Example 3, and 14.20° for Example 4, respectively, and no clear peak shift due to the addition of Pd was confirmed for MoS2 in Synthesis Example 1. From this, it is inferred that there has been no significant change in the crystal structure of the molybdenum disulfide particle portion of the composite from the molybdenum disulfide particles in Synthesis Example 1, which are the raw material. Furthermore, in a state in which metal ions are distributed between layers of the material shown in Patent Document 1, the layer spacing of MoS2 usually changes. However, in the composite particles of Examples 1 to 4, no peak shift of 2θ=14.4±0.5° was observed as described above, and it was confirmed that, unlike the state shown in Patent Document 1, the layer spacing of MoS2 did not change.
[0211] In addition, according to the results of surface analysis of the composite particles of Examples 1 to 4 by X-ray photoelectron spectroscopy (XPS), the peak position value (binding energy value) of the Pd 3d spectrum was 5 / 2 : 335.5 eV, Pd 3d 3 / 2 The bond energy was 340.8 eV, and the valence of Pd was found to be zero based on these bond energy values. This suggests that the palladium contained in the composite particles of Examples 1 to 4 differs from the state shown in Patent Document 1 in that palladium ions are not distributed between the layers of molybdenum disulfide.
[0212] Figure 5 shows an HAADF-STEM image (transmission electron image, JEM-ARM300F, manufactured by JEOL Ltd.) and an SEI image (secondary electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of the composite particle of Example 2. The arrows in Figure 5 indicate an example of the same palladium particle observed in the HAADF-STEM image and the SEI image. A transmission electron image provides information about the surface of the sample (including the backside of the grains in the image) and the inside of the sample, while a secondary electron image provides information about the outermost surface of the sample (not including the inside or backside of the grains in the image). A comparison of the transmission electron image and the secondary electron image revealed that a large number of palladium particle images were also observed in the secondary electron image, indicating that the majority of palladium particles were present on the surfaces of the molybdenum disulfide particles.
[0213] From the above, it was discovered that the Pd in the composite particles of Examples 1 to 4 does not have the crystal structure of palladium metal crystals, and is present as palladium particles on the surface of molybdenum disulfide particles in the form of an aggregate of zero-valent palladium atoms that do not have a crystal structure.
[0214] If Pd is doped into MoS2, and Pd replaces Mo in the crystal structure, or if Pd exists as ions between layers, most of the Pd atoms in the particle will exist inside the MoS2. On the other hand, in the composite particles of each Example, most of the Pd atoms contained in the composite particles constitute palladium particles and are considered to be present on the surface of the composite particles.
[0215] (Catalyst ink manufacturing) Inks were produced using the particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 and 2 as raw materials, and their catalytic performance in the hydrogen evolution reaction (HER) was evaluated by the following method.
[0216] 4 mg of the particles obtained above (any of the particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 to 2) and carbon black (Ketjen Black, manufactured by Lion Specialty Chemicals Co., Ltd., product number: EC300J, median diameter D 50An ink (dispersion) was produced by mixing 2 mg of 1000 nm (40 nm), 40 μL of 5% Nafion dispersion (FUJIFILM Wako Pure Chemical Industries, Nafion dispersion solution), and 1 mL of ethanol, and dispersing the particles by ultrasonic treatment for 1 hour. 20 μL of the obtained ink was applied to the electrode surface, and the surface liquid was naturally dried, then transferred to a vacuum dryer and dried at 60 °C for 6 hours or more to obtain a test electrode. The hydrogen evolution reaction (HER) activity of the obtained test electrode was evaluated using a three-electrode method. The evaluation conditions were an LSV method with a scan voltage range of -0.3 V to 0 V and a scan speed of 5 mV / S.
[0217] The evaluation results of the above catalyst performance are shown in Table 1.
[0218] The inks containing the composite particles of Examples 1 to 4 had a current density of 10 mAcm compared to the inks containing the particles of Synthesis Example 1 or Comparative Examples 1 and 2. -2 The overvoltage value at −0.3 V was low (measurement was not possible in Comparative Example 2), and the current density value at −0.3 V was high.
[0219] From the above, it was demonstrated that the composites of Examples 1 to 4 in which molybdenum disulfide particles and palladium particles were composited together were capable of exhibiting excellent catalytic activity.
[0220] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Explanation of symbols]
[0221] 1 Manufacturing equipment 2. Firing furnace 3 Cooling piping 4. Collection Machine 5. Exhaust port 6 Opening adjustment damper 7 Observation window 8 Ventilation device 9 External cooling device
Claims
1. Molybdenum disulfide particles and palladium particles, the palladium particles are present on the surface of the molybdenum disulfide particles and include aggregates of palladium atoms having no crystal structure, the palladium particles have an average particle size of 20 nm or less, The specific surface area measured by the BET method is 10 m 2 / g or more 200m 2 / g or less, The molybdenum disulfide particles contain molybdenum disulfide, and the average crystallite size determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement is 150 nm or less. A composite, wherein the ratio of the palladium content to the total mass of the composite, as determined by XRF analysis, is 0.1 mass% or more.
2. The median diameter D of the complex determined by dynamic light scattering 50 The complex of claim 1, wherein the diameter of the complex is 1000 nm or less.
3. 3. The composite of claim 1 or 2, wherein the molybdenum disulfide contained in the molybdenum disulfide particles comprises a 3R crystal structure.
4. 3. The composite according to claim 1, wherein the primary particles of the molybdenum disulfide particles have a shape of a cord, ribbon or sheet and an average thickness of 50 nm or less.
5. A hydrogen generation catalyst comprising the composite according to claim 1 or 2.
6. The hydrogen generation catalyst according to claim 5 , further comprising a conductive material.
7. A catalyst ink comprising the composite according to claim 1 or 2 and a solvent.
8. The catalyst ink of claim 7 further comprising a polyelectrolyte.
9. The catalyst ink of claim 7 further comprising a conductive material.
10. 3. A method for producing the composite according to claim 1, comprising the step of mixing molybdenum disulfide particles with a palladium solution.
Citation Information
Patent Citations
Metal cation doped molybdenum disulfide material, preparation method and applications thereof
CN106608652A
Petal-shaped microsphere molybdenum disulfide composite carbon material loaded Pd metal catalyst and preparation method thereof
CN111146455A
Monatomic metal-molybdenum sulfide nano-composite as well as preparation method and application thereof
CN112774697A
Composite nano material as well as preparation method and application thereof
CN114772643A
Catalyst electrode for producing hydrogen and method of manufacturing the catalyst electrode
KR1020210130930A
